2019
DOI: 10.1111/epi.14933
|View full text |Cite
|
Sign up to set email alerts
|

Early recovery of interhemispheric functional connectivity after corpus callosotomy

Abstract: Objective To investigate whether interhemispheric functional connectivity (FC) recovers in the first year after total callosotomy. Methods Eight epilepsy patients undergoing total callosotomy were recruited. Resting‐state functional magnetic resonance imaging was acquired before and after surgery. The precallosotomy and postcallosotomy interhemispheric and intrahemispheric FC was analyzed by using graph theory and voxel‐mirrored homotopic connectivity (VMHC). The seizure outcome was scored using the Engel surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…First, the cortical homotopic regions connected by CC sub-regions 2 (premotor and supplementary motor cortices) and 5 (parietal, temporal, and occipital cortices) are much larger than the significant clusters identified in the voxel-wise VMHC correlation analyses, which may lead to a disproportional change pattern of the measured functional and structural connectivity. Second, although the CC serves as the major pathway for inter-hemispheric information transfer (58,59), there is mounting evidence that other pathways contribute to inter-hemispheric synchronization, e.g., intact functional coupling between the hemispheres in individuals with complete agenesis of the CC (60) and early recovery of inter-hemispheric functional connectivity in epilepsy patients after total corpus callosotomy (61).…”
Section: Discussionmentioning
confidence: 99%
“…First, the cortical homotopic regions connected by CC sub-regions 2 (premotor and supplementary motor cortices) and 5 (parietal, temporal, and occipital cortices) are much larger than the significant clusters identified in the voxel-wise VMHC correlation analyses, which may lead to a disproportional change pattern of the measured functional and structural connectivity. Second, although the CC serves as the major pathway for inter-hemispheric information transfer (58,59), there is mounting evidence that other pathways contribute to inter-hemispheric synchronization, e.g., intact functional coupling between the hemispheres in individuals with complete agenesis of the CC (60) and early recovery of inter-hemispheric functional connectivity in epilepsy patients after total corpus callosotomy (61).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study reported the recovery of the interhemispheric pathway within the first year following corpus callosotomy in epilepsy patients (Hung et al . 2019). Structural strengthening of the pathways between the motor areas and the cerebellum was reported in a complete commissurotomy patient, indicating that structural compensation is possible (Nomi et al .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the overall network topology of FC in AgCC subjects, we adopted a graph-theoretic approach ( Hung et al, 2019 ). For the region of interest (ROI) based network analyses, the mean time course was extracted from 116 cortical and subcortical ROIs from the automatic anatomic labeling (AAL) atlas.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, we used topographic theory on DTI and rs-fMRI data to study the global SC and FC at the network level in AgCC and HC. VMHC quantifies the FC between each voxel in one hemisphere and its mirrored counterpart in the other hemisphere ( Hung et al, 2019 , Owen et al, 2013b , Ridley et al, 2016 ). Graph-based approaches model the brain as a complex network represented graphically by a collection of nodes and edges.…”
Section: Introductionmentioning
confidence: 99%